2009
DOI: 10.1002/jbm.b.31555
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillogenesis in continuously spun synthetic collagen fiber

Abstract: The universal structural role of collagen fiber networks has motivated the development of collagen gels, films, coatings, injectables, and other formulations. However, reported synthetic collagen fiber fabrication schemes have either culminated in short, discontinuous fiber segments at unsuitably low production rates, or have incompletely replicated the internal fibrillar structure that dictates fiber mechanical and biological properties. We report a continuous extrusion system with an off-line phosphate buffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 57 publications
5
95
1
Order By: Relevance
“…A recent report of Caves et al has addressed this limitation via the use of an off-line fibrillogenesis process to reduce the time and space required for a continuous fibre extrusion process and reporting a production rate of 60 m h À1 to form D-banded collagen fibres, confirmed via TEM and shown in Fig. 2C [57]. However, in all cases, the quantification of gelatine within the final collagen fibre remains an area of experimental difficulty for all the systems discussed.…”
Section: Fabrication Of Assembled Microfibres From Acidified Collagenmentioning
confidence: 71%
“…A recent report of Caves et al has addressed this limitation via the use of an off-line fibrillogenesis process to reduce the time and space required for a continuous fibre extrusion process and reporting a production rate of 60 m h À1 to form D-banded collagen fibres, confirmed via TEM and shown in Fig. 2C [57]. However, in all cases, the quantification of gelatine within the final collagen fibre remains an area of experimental difficulty for all the systems discussed.…”
Section: Fabrication Of Assembled Microfibres From Acidified Collagenmentioning
confidence: 71%
“…Extrusion or electrospinning of collagen solutions [26, 27] are other methods of making collagen fibers with different thicknesses ranging from nano to micron size scales. Extrusion process can generate threads only whereas the electrospinning can denature collagen [15].…”
Section: Discussionmentioning
confidence: 99%
“…(Cheng et al, 2008). To our knowledge, ELAC is amongst the strongest collagen-based biomaterials reported to date (Table 1) (Awad et al, 2003;Caves et al, 2010;Pins et al, 1997;Srinivasan and Sehgal, 2010;Tohyama and Yasuda, 2000;Wang et al, 1994a;Wren et al, 2001). Therefore, ELAC threads have significant potential to replace damaged tendons and be used in the regeneration bone-tendon interfaces.…”
Section: Discussionmentioning
confidence: 90%
“…Microfluidic alignment is one of the most successful ones; however, alignment efficiency of threads is reduced with increasing channel width. Recently, (Caves et al, 2010) demonstrated only a partial alignment following syringe extrusion and that a mechanical stretch is needed in addition to syringe extrusion to obtain full alignment.…”
Section: Introductionmentioning
confidence: 99%